2011
DOI: 10.1002/mus.21871
|View full text |Cite
|
Sign up to set email alerts
|

Twitch potentiation induced by stimulated and voluntary isometric contractions at various torque levels in human knee extensor muscles

Abstract: The purpose of this study was to compare the extent of twitch potentiation (TP) after stimulated or voluntary contractions at identical intensities for the human knee extensor muscles. Isometric knee extensions of 10 s were performed at 20%, 40%, and 60% of maximal voluntary contraction (MVC) torque level, through percutaneous electrical stimulation of the quadriceps at 80 Hz or voluntary contraction. Twitch responses were evoked by stimulating the femoral nerve percutaneously with supramaximal intensity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…Namely, although submaximal contractions have so far been used as warm-up procedures to reduce fatigue, the current results indicate that high-intensity short-duration contractions can be a more effective warm-up modality for high-power activities. In addition, considering the present fmdings with our previous results (22,25), we can recommend the use of NMES with proper duration, intensity, and stimulation frequency as a more immediately effective warm-up modality for explosive sports activities. Furthermore, the current fmdings can provide an evidence for the effectiveness of complex training, which has been defined as combining plyometric and weight resistance exercises in the same training session, and help to establish proper protocols (i.e., rest interval between plyometdc and weight resistance exercises) in this training style.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Namely, although submaximal contractions have so far been used as warm-up procedures to reduce fatigue, the current results indicate that high-intensity short-duration contractions can be a more effective warm-up modality for high-power activities. In addition, considering the present fmdings with our previous results (22,25), we can recommend the use of NMES with proper duration, intensity, and stimulation frequency as a more immediately effective warm-up modality for explosive sports activities. Furthermore, the current fmdings can provide an evidence for the effectiveness of complex training, which has been defined as combining plyometric and weight resistance exercises in the same training session, and help to establish proper protocols (i.e., rest interval between plyometdc and weight resistance exercises) in this training style.…”
Section: Discussionsupporting
confidence: 63%
“…3). This observation seems to be puzzling because the extent of TP is influenced by the number and fype of muscle fibers recmited during conditioning contractions (17,25,40). However, the difference in target torque levels does not necessarily correspond with that in the number of muscle fibers recruited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The joint torque generated by twitch contraction is increased after brief voluntary 1–3 and stimulated contractions 4–6. This phenomenon is collectively referred to as twitch potentiation (TP).…”
mentioning
confidence: 99%
“…Only a few investigations have compared the extent of TP elicited after voluntary and NMES at high‐stimulation‐frequency (80–100 H Z ) conditioning contractions at equivalent target levels. 4, 14, 15 Requena et al compared the extent of TP after voluntary vs. NMES contractions at 25% of maximal voluntary contraction (MVC) torque level, and demonstrated that the extent of TP after a 7‐s NMES at 100 H Z was greater than that after a 7‐s voluntary contraction in knee extensor muscles 15. In contrast, Jubeau et al showed that a 10‐s NMES of the quadriceps femoris at 100 H Z with 40% MVC torque induced a smaller TP than a 10‐s voluntary contraction 14.…”
mentioning
confidence: 99%